ADHD and Oppositional Defiant Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The outcome of 131 children with ADHD (101 males, 30 females; mean age 5 years, range 3 to 7 years) with and without oppositional defiant disorder (ODD) was determined in a prospective study at the University of Goteborg, Sweden.